SYNTHESIS AND IMMOBILIZATION OF CAPTOPRILIN HYDROGEL POLYVINYL ALCOHOL-POLYVINYL PIRROLIDONE PREPARED BY FREEZING-THAWAND GAMMA RADIATION - Erizal Erizal; Darmawan Darmawan; Sudirman Sudirman; Sudaryanto Sudaryanto (Jurnal Sains Materi Indonesia, 2013)
SYNTHESIS AND IMMOBILIZATION OF CAPTOPRILIN HYDROGEL POLYVINYL ALCOHOL-POLYVINYL PIRROLIDONE PREPARED BY FREEZING-THAWAND GAMMA RADIATION. In order to apply the hydrogel as a matrix for controlled drug release, the polyvinylalcohol (PVA)-polyvinyl pirrolidone (PVP) hydrogels have been synthesized and used for immobilization of captopril. The mixture of PVA-PVP solution containing captopril were freezing and thawing followed by gamma irradiation from Co-60 with the doses of 10 kGy, 20 kGy and 30 kGy. The water absorption and gel fraction of hydrogels were measured gravimetrically. The chemical changes of hydrogels were determined using Fourier Transform Infrared (FT-IR) spectrometer. The release of captopril were monitored using Ultra Violet-Visible (UV-Vis) spectrophotometer. It was found that with increasing cycled of freeze-thawing and irradiation dose up to 30 kGy, gel fraction and water absorption of hydrogels increase. FT-IR spectra demonstrated that there was strong intermolecular crosslinking between the PVAand PVP. The release rate of captopril from hydrogel increases with increasing irradiation dose. The release pattern indicates that the captopril released in medium were with zero order during most of the release period and generally with burst effect. The results suggest that crosslinked PVA-PVP hydrogels are suitable for controlled release of drug.